Strategi Guru Dalam Menumbuhkan Karakter Islami Siswa MA Nurul Munawarah Kelurahan Tumbang Lahung - Akhmad Febio Quari Noor Rohim; Sardimi Sardimi; Saiful Lutfi (Kamaya: Jurnal Ilmu Agama, 2026)
Teachers’ strategies for fostering Islamic character in students are essential for educational institutions, particularly Islamic schools; however, at MA Nurul Munawarah, there are still some students who engage in behaviors contrary to the Islamic character expected of a student. This study aims to determine the strategies teachers use to foster Islamic character at MA Nurul Munawarah in Tumbang Lahung Village. This study employs a qualitative approach using data collection techniques such as observation, interviews, and documentation. The results indicate that through various routine guidance programs such as congregational Dhuha prayer, group Quran recitation, religious lectures, and other religious activities which are not only participated in by students but also by teachers as their mentors, students’ active engagement in these religious activities demonstrates that consistent routine-based strategies can instill Islamic values. The main factors that can influence students’ Islamic character include the family, community, and school environments. This study concludes that the implementation of teachers’ strategies is crucial in fostering Islamic character through various methods, such as setting a good example and instilling religious activities, thereby aligning with the school’s Islamic-based vision and mission.